(untitled) (Bangladesh Journal of Medical Science, 2020)
Objective: Concealed pregnancy is a public health concern with risks to girl-education as well as maternal and child health. This paper focuses on concealed pregnancy amongst adolescents attending schools in Limpopo province of South Africa. It defines concealed pregnancy, some reasons for concealment, methods used, partners in crime and implications for girl-education as well as maternal and child health. Materials and methods: A qualitative and exploratory study using in-depth interviews with 10 pregnant adolescents attending school, five parents and 10 educators on their experiences of caring for pregnant adolescents attending school was conducted. Results and Discussion: Results show that pregnant adolescents attending school conceal their pregnancies using various methods of keeping a secret, telling a lie, wearing baggy clothing, isolating and hiding among other students in overcrowded teaching spaces. They participate passively in learning activities to evade attention to themselves. Some authority figures such as educators and parents as well as other students are accomplices. Conclusion: To conceal pregnancies, pregnant adolescents attending schools flout antenatal care, thus increasing risks to women and children’s health. They also show lack of attentiveness to learning activities at school, thus losing chances to achieve an education. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.620-624